THE COST OF TREATMENT FOR PEDIATRIC TUBERCULOSIS PATIENTS: A CROSS-SECTIONAL STUDY - Sinta Dewi Lestyoningrum; Adistha Eka Noveyani; Wahyu Gito Putro; Debri Riski Faisal; Yuni Purwatiningsih; Muhammad Agus Mikrajab; Wahyu Pudji Nugraheni (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: Tuberculosis (TB) is a leading global communicable disease. Pediatric tuberculosis, in particular, is prevalent among the population aged 0-14 years and necessitates a treatment duration of at least six months. Aims: This study aims to assess the total treatment cost of pediatric tuberculosis patients and determine the factors associated with the total cost. Methods: A cross-sectional design was employed to collect the retrospective data at a public hospital and PHC in the province-level Special Region of Yogyakarta, Indonesia. Treatment costs are categorized into the following: laboratory costs, professional costs, drug costs, medical and non-medical support costs, and miscellaneous costs. The collected data underwent both descriptive and statistical analysis using regression methods, namely logistic and probit regressions. Results: The analysis revealed that most patients were between 0 and 2 years old and most of them are school-age, with an average treatment cost of USD 62.80 per patient. The study identified laboratory costs (RR 0.198; 95% CI 0.083-0.314), professional costs (RR 9.402; 95% CI 4.108-14.698), drug costs (RR 5.269; 95% CI 2.326-8.212), and medical support costs (RR 0.223;95% CI 0.064-0.382) as the primary contributors to the total cost. Conclusion: The point of this study is that effective treatment is possible with proper financial support. To achieve a successful outcome in treating pediatric tuberculosis, it is imperative to establish an advocacy and collaboration effort to enhance the primary health services. This cooperative effort should prioritize convenient access to treatment and enhancing active case finding. Keywords: cost of illness, cost of treatment, pediatric tuberculosis